Optimizing fitness: plastic flowering time in variable environments - Dong, Wei; Zhang, Yalin; Xing, Yue; Chang, Kexin; Qiu, Nianwei; Song, Yuguang (Frontiers in Plant Science, 2025)
Flowering time is a critical determinant of crop yield and adaptability, regulated by the integration of environmental cues, phytohormones, and genetic networks. Abiotic stresses such as drought, waterlogging, salinity, and high temperature, together with biotic stresses including pathogens, viruses, and herbivores, profoundly reshape flowering phenology through microRNAs, transcription factors, epigenetic modifications, and hormonal crosstalk. Phytohormones, especially ABA and GA, act as regulatory hubs coordinating stress adaptation and floral transition, though their effects vary across species and conditions. This review synthesizes recent advances in stress-mediated flowering regulation and emphasizes the challenges of balancing stress tolerance with yield stability. We propose that integrating multi-omics data, regulatory network modeling, and artificial intelligence will accelerate the breeding of stress-resilient cultivars with stable productivity.